Practical Recommendations for the Preoperative Screening and Protective Protocols in Cancer Surgeries During COVID-19: A Systematic Review - Dorri, Sara; Sari, Fateme; Seyedhasani, Seyedeh Nahid; Atashi, Alireza; Hashemi, Esmatalsadat; Olfatbakhsh, Asiie (Frontiers in Surgery, 2021)
Introduction: The new coronavirus (SARS-CoV-2) has emerged many new challenges to the health care and timing of surgical care. Although many guidelines recommended postponing elective surgical procedures, modifications in cancer procedures and individualized treatment must be considered. The aim of this systematic review was to outline a guideline for preoperative screening before cancer surgeries and protecting health care workers during the pandemic. Materials and Methods: This study was conducted through a search in electronic databases up to August 2020. PubMed, EMBASE, Web of Science, Scopus, Science Direct, and Google Scholar databases were searched without time limitation. The keywords were combination of preoperative, cancer surgery, COVID-19 and their synonyms. Results: The most commonly used ways to triage preoperatively were telephone pre- assessment for suspicious symptoms and history of contact or travel, 14- day self- Isolation, in- hospital queries at admission, temperature monitoring and isolation in a single room COVID- free ward or physical distancing. RT-PCR test 24-72 hours before operation was recommended commonly except in un-accessible centers but non- contrast Chest- CT scan is not routinely advised for elective surgeries to salvage medical resources. Recommended Personal Protective Equipment for staffs were wearing N95 mask in addition to gown, gloves, eye protection in Aerosol-generating procedures (AGPs) and wearing gloves, hats, and disposable surgical masks, practice distancing and hand hygiene for all staffs. Meanwhile team separation of hospital staffs caring for COVID-19 patients, segregated areas for COVID-19 clean and contact, restriction of visitors and family members and personal distancing are mostly recommended. Conclusion: We hope this review would be a guidance for triage, preoperative testing and summarizing safety principles during COVID-19 pandemic alongside with surgical reintegration.